Kedudukan Perempuan dalam Masyarakat Multikultur, Pada Trilogi Novel Sembalun Rinjani Karya Djelantik Santha - I Gede Gita Purnama A.P (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Women have been filling the literary space of modern Balinese literature as an object of storytelling. The role and appearance of women who have been in the hegemony of patriaki has always been interesting to talk about from a feminist point of view. The novel trilogy of Sembalun Rinjani is one of the modern Balinese literary novels depicting the position of women in a multicultural society. This novel by Djelantik Santha reflects the duality of the struggle of female characters in multicultural society to escape from the stigma of inferior creatures, as well as the image of female characters who still survive in the hegemony of patriaki.